The Influence of Publicity and Direct Marketing Towards Market Targets at PT. Hidiri Indonesia Cemerlang - Aryani Sairun; Sugito Sugito (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
The purpose of this study was to determine the effect of publicity on the target market at PT. Hidiri Indonesia Cemerlang. To determine the effect of direct marketing on the target market at PT. Hidiri Indonesia Cemerlang. To determine the effect of publicity and direct marketing on the target market at PT. Hidiri Indonesia Cemerlang. The population taken was 154 people and 111 people were sampled using the slovin method. The results showed that Publicity had a significant effect on the target market (accept Ha , reject Ho). Direct marketing had a significant effect on the target market (accept Ha , reject Ho). Simultaneously, the variables of publicity and direct marketing had a significant effect on the target market. It can be concluded that the hypothesis of this study can be accepted, namely: "Publicity and direct marketing have a significant effect on the target market (accept Ha and reject Ho)".